Enhancing Legal Certainty through Legal Reform in Indonesia: Problems and Efforts to Strengthen Legal Institutions - Siddiq, Nurman; Salam, Rudhiana (Strata Law Review, 2025)
Legal certainty is a fundamental aspect of the rule of law in Indonesia, as mandated in the 1945 Constitution. However, legal uncertainty persists due to the weakness of legal institutions, which undermines public trust, social stability, and economic growth. This study explores the challenges faced by key legal institutions—police, prosecutor’s office, and judiciary—and their impact on legal certainty. The research employs a normative legal method with a conceptual approach, analyzing secondary legal sources to assess the effectiveness of legal enforcement mechanisms. Findings indicate that corruption, inadequate infrastructure, limited human resource capacity, and inefficient judicial processes hinder the ability of these institutions to uphold justice. To address these issues, comprehensive legal reforms are essential, focusing on enhancing institutional capacity, enforcing transparency and accountability, integrating technology, and fostering public participation. Strengthening oversight mechanisms and implementing ethical standards for law enforcement officials are also crucial. By adopting these measures, Indonesia can build a more transparent, effective, and just legal system that upholds the rule of law and restores public confidence.